1999
DOI: 10.1002/(sici)1097-4547(19991015)58:2<308::aid-jnr11>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Aging in a dish: Age‐dependent changes of neuronal survival, protein oxidation, and creatine kinase BB expression in long‐term hippocampal cell culture

Abstract: Results from different experimental systems demonstrate that increased oxidative damage plays a role in normal aging and age-associated pathology. In the current study, long-term cultures of hippocampal neurons were examined as a model system. It was established that neuronal survival in long-term culture decreases according to the Gompertz law and that neuronal "aging in the dish" is associated with increased oxidative damage of cell proteins. The increase of protein carbonyl formation in aged neurons was dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 55 publications
6
41
0
Order By: Relevance
“…Some research on neuron senescence has been carried out in long-term cultures of primary neurons and collected data seem to suggest that such cultures can be used as a model of neuronal aging [6, 7]. Overall, neurons can be kept alive for as long as 60 days, during which time, they display signs of development, maturation and finally aging and death.…”
Section: Introductionmentioning
confidence: 99%
“…Some research on neuron senescence has been carried out in long-term cultures of primary neurons and collected data seem to suggest that such cultures can be used as a model of neuronal aging [6, 7]. Overall, neurons can be kept alive for as long as 60 days, during which time, they display signs of development, maturation and finally aging and death.…”
Section: Introductionmentioning
confidence: 99%
“…Andres et al (2008) studied that creatine kinase/phosphocreatine system plays a key role in cellular energy buffering and energy transport particularly in cells with high and fluctuating energy requirements like neurons. The ATP binding domain of brain-specific creatine kinase contains essential arginine, histidine, lysine, and cysteine residues that may be targeted by ROS (Aksenova et al 1999). Koufen and Stark (2000) demonstrated that direct oxidation of sulphydryl groups in cysteines located in the active site of creatine kinase also may inactivate the enzyme.…”
mentioning
confidence: 99%
“…Age-dependent increases in the density of Ca 2+ channels in long-term culture of hippocampal cells have been reported to be analogous to patterns seen in neurons of in vivo aged animals (Porter et al, 1997). Age-dependent changes of neuronal survival, protein oxidation and creatine kinase BB expression in long-term hippocampal cell culture have also been described as aging in dish (Aksenova et al, 1999). Using long-term mesencephalic culture, Troadec and coworkers demonstrated that noradrenaline promotes survival and function of dopaminergic neurons (Troadec et al, 2001).…”
Section: Prolongation Of Neuronal Survival Bymentioning
confidence: 78%
“…A complex of genetic, programmed, and variable factors producing the age-related changes affect retinal neuronal survival and can result in retinal neuronal degeneration. Long-term neuronal culture has been used as an aging and neurological research tool for understanding the changes of aging, their impact on disease, and for the development of agents able to modify agerelated changes and to prevent neurodegeneration (Kuroda et al, 1995;Puttfarcken et al, 1996;Aksenova et al, 1999;Troadec et al, 2001). Age-dependent increases in the density of Ca 2+ channels in long-term culture of hippocampal cells have been reported to be analogous to patterns seen in neurons of in vivo aged animals (Porter et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation